Immuno-metabolic dendritic cell vaccine signatures associate with overall survival in vaccinated melanoma patients - Adamik, Juraj; Munson, Paul V.; Maurer, Deena M.; Hartmann, Felix J.; Bendall, Sean C.; Argüello, Rafael J.; Butterfield, Lisa H. (Nature communications, 2023)
Efficacy of cancer vaccines remains low and mechanistic understanding of antigen presenting cell function in cancer may improve vaccine design and outcomes. Here, we analyze the transcriptomic and immune-metabolic profiles of Dendritic Cells (DCs) from 35 subjects enrolled in a trial of DC vaccines in late-stage melanoma (NCT01622933). Multiple platforms identify metabolism as an important biomarker of DC function and patient overall survival (OS). We demonstrate multiple immune and metabolic gene expression pathway alterations, a functional decrease in OCR/OXPHOS and increase in ECAR/glycolysis in patient vaccines. To dissect molecular mechanisms, we utilize single cell SCENITH functional profiling and show patient clinical outcomes (OS) correlate with DC metabolic profile, and that metabolism is linked to immune phenotype. With single cell metabolic regulome profiling, we show that MCT1 (monocarboxylate transporter-1), a lactate transporter, is increased in patient DCs, as is glucose uptake and lactate secretion. Importantly, pre-vaccination circulating myeloid cells in patients used as precursors for DC vaccine generation are significantly skewed metabolically as are several DC subsets. Together, we demonstrate that the metabolic profile of DC is tightly associated with the immunostimulatory potential of DC vaccines from cancer patients. We link phenotypic and functional metabolic changes to immune signatures that correspond to suppressed DC differentiation. Efficacy of dendritic cell (DC)-based vaccines remains unsatisfactory. Here the authors analyse the transcriptomic and immune-metabolic profiles of DCs from patients enrolled in a DC vaccine trial in late-stage melanoma, suggesting that the metabolic profile of DC is associated with the immunostimulatory potential of the cancer vaccine.